2002
DOI: 10.1016/s0043-1648(02)00163-1
|View full text |Cite
|
Sign up to set email alerts
|

Contact fatigue failure modes of HVOF coatings

Abstract: The objective of this experimental study was to investigate the influence of coating thickness and contact stress fields on the performance and fatigue failure modes of thermal spray (WC-12%Co) HVOF coatings. Results of this study indicate that a non-dimensional coating thickness parameter (∆ = ξ/Ψ ), where ξ is the coating thickness and Ψ the depth of maximum shear stress, can be used as a useful index to optimise coating delamination resistance during Hertzian contact loading. Apart from the detection of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Previous studies by Ahmed [7] showed that delamination was the commonly failure mode of the coated specimens in rolling contact. The coating is either delaminated at a location within the coating or just at coating/substrate interface.…”
Section: S-n Curvesmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies by Ahmed [7] showed that delamination was the commonly failure mode of the coated specimens in rolling contact. The coating is either delaminated at a location within the coating or just at coating/substrate interface.…”
Section: S-n Curvesmentioning
confidence: 95%
“…Previous studies showed that the RCF failure modes of the spray coatings could be categorized into four types and named as surface abrasion, spalling, cohesive delamination (i.e., delamination within coating), and bulk failure (i.e., interfacial delamination) [4]. Table 1 summarizes the typical RCF test results from the published literature [1,4,[7][8][9][10][11][12][13][14][15][16][17]. These results are present in terms of deposition process, coating hardness, coating material, thickness and the contact stress.…”
Section: Introductionmentioning
confidence: 99%
“…The rough contact between the coating and the surface of the work piece and the micro sliding in the contact region make the coating prone to plastic deformation and micro shear. Therefore, it is necessary to study the lubrication state between the wedges and the inner and outer rings [5] . An empirical formula for calculating the oil film thickness, m h , between wedges and the inner and outer rings is presented as follows: …”
Section: Spalling Reason Analysismentioning
confidence: 99%
“…As a result, pitting will appear owing to the surface material falling out. 20,21 Rollers of the tester are made of GCr15 bearing steel. It attaches to high-carbon chromium bearing steel, which has good performance and wide applications.…”
Section: Wear Testsmentioning
confidence: 99%